Age Related Changes in Pinealocytes of the Pineal Gland in Bangladeshi Cadavers - Afroz, Halima; Nurunnabi, Abu Sadat Mohammad; Rahman, Mushfika; Fatema, Kanij; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2016)
Background: The pineal gland (epiphysis cerebri) contains cords and follicles of pinealocytes and neuroglia. Objective: To determine the number of the pinealocytes and neuroglial cells per sq. mm of microscopic field in different age group in a Bangladeshi population to view the age related change. Methods: This cross-sectional study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2009 to June 2010, based on the collection of 60 pineal glands from whole human brains of unclaimed dead bodies from the morgue. All the samples were divided into four age-groups: 15-30 years, 31-40 years, 41-50 years and >50 years. Histological slides were prepared by using routine Harris Haematoxylin and Eosin (H & E) stain. The number of pinealocytes and neuroglial cells per sq. mm of the microscopic field were determined by point counting technique, using ocular micrometer. For statistical analysis, ANOVA and independent sample t test were used. Results: The mean number of pinealocytes and neuroglial cells were found 10875.00±649.75 and 606.31±94.52 in group15-30 years, 9738.83±761.35 and 631.57±94.52 in group31-40 years 31-40 years, 9637.78±382.02 and 568.41±69.57 in group 41-50 years and 8134.64±358.07 and766.31±248.00 in group >50 respectively. Age related significant differences were found in number of pinealocytes in 15-30 years vs 31-40 years, 15-30 years vs 41-50, 15-30 years vs >50, 31-40 years vs >50 and 41-50 vs >50 years. However, no differences were found in number of neuroglial cells among different age groups. Conclusion: This study showed progressive degeneration of pinealocytes with advancing age. However, no age related changes were found in number of neuroglial cells. Bangladesh Soc Physiol. 2016, June; 11(1): 18-22